From Offshoring to Reshoring: Re-emerging Trends - Lempard, Nicholas (2017)
Over the last forty years, manufacturing has witnessed exponential growth in offshoring to low-cost countries, as part of a cost leadership strategy (Porter, 1985). However a re-evaluation of the cost-benefits of offshoring has signalled a decline in value, and unveiled reshoring as a highly viable alternative; especially following the introduction of new, innovative technology.